A descriptive analysis of predoctoral surgical requirements in US dental schools in 2020. Issue 4 (26th November 2021) - Bello, Angel S.; Ray, Nicholas; Shearer, Thomas R.; Govind, Akshay
Abstract: Objectives: This study aims to describe surgical graduation requirements in US dental schools in 2020, including changes made due to the COVID‐19 pandemic. Methods: Representatives of Commission on Dental Accreditation‐approved predoctoral dental programs in the US ( n = 66) received a 13‐item questionnaire about operative and observational surgical requirements. Responses were assigned values to tabulate a surgical score (zero‐ to eight‐point scale) as a proxy for required surgical experience, and statistical analyses were performed to explore for predictors. Results: Surveys were returned by 97% (64/66) of programs with complete data from 62.5% of responding institutions. In periodontics, 6.8% of programs require students to perform periodontal surgery, 63.8% to assist, and none require a competency assessment in periodontal surgery. In oral and maxillofacial surgery, 23.3% of programs have numerical requirements in performance of surgical extractions, 35% require an operating room experience, and 51.9% have a competency assessment involving a surgical procedure. Modifications to surgical and nonsurgical graduation requirements due to COVID‐19 were reported by 51.6% and 52.5% of programs, respectively. The mean surgical score was 1.73 ± 1.2 (range = 0–4) of eight possible points. This was not predicted by class size or the presence of postgraduate surgical programs. The presence of postgraduate surgical programs roughly doubled the likelihood of requiring an observational experience in surgery. Conclusions: As of 2020, US dental programs require a small fraction of surgical experiences available to students. Class size is not a predictor of required surgical experience. The presence of postgraduate surgical programs increased the likelihood of required observational experiences.